THE BENEFITS OF JOINING ENGLISH DEBATING SOCIETY (EDS) FOR STUDENTS SPEAKING SKILLS - Hetharie, Arline Thinesia; Listyani, Listyani; Setyarini, Maria Christina Eko (LLT Journal: A Journal on Language and Language Teaching, 2020)
This qualitative research study aims to analyze the benefits of joining debating club to enhance students speaking skill. The data were collected from semi-structured interviews to inquire students perceptions who performed the most outstanding progress after joining in debating club batch 2014 in UKSW. The research questions used on this study were what are the benefits of joining debating club on speaking skills and how could the debating club enhance the speaking skills. The findings show that there were five aspects of speaking skill and three others soft skill enhanced through debating method. Those skills are fluency, vocabulary, comprehension of the essence of debates, pronunciation, grammar, critical thinking, collaborative learning, and problem solving. The skills were improved though the drilling practices and materials on learning process. The significance of this study is to prove the significant improvement of using debating method to enhance students speaking skill.